ChemInform Abstract: On the Synthesis, Characterization and Magnetic Properties of Two New Phases Discovered in the PbO—Fe2O3—P2O5 System. Issue 31 (11th July 2013) - El Hafid, Hassan; Velazquez, Matias; Perez, Olivier; El Jazouli, Abdelaziz; Pautrat, Alain; Decourt, Rodolphe; Veron, Emmanuel; Viraphong, Oudomsack; Delmas, Claude
Abstract PbFe3O(PO4)3 (I) powder is prepared by co‐precipitation from an aqueous solution of Pb(NO3)2, Fe(NO3)3, and (NH4)2HPO4 at 120 °C (precipitate heating to 1.